Oblicz korzystając ze wzorów skróconego mnożenia.

Oblicz Korzystając Ze Wzorów Skróconego Mnożenia class=

Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

a)

(√2 + √8)² = (√2)² + 2 * √2 * √8 + (√8)² = 2 + 2√(2*8) + 8 = 2 + 2√16 + 8 = 2 + 2 * 4 + 8 = 2 + 8 + 8 = 18

b)

(√3 + 2√6)² = (√3)² + 2 * √3 * 2√6 + (2√6)² = 3 + 2*2√(3*6) + (4*6) = 3 + 4√18 + 24 = 3 + 4√(3²*2) + 24 = 3 + 4*3√2 + 24 = 27 + 12√2

c)

(√10 - √3)(√10 + √3) = (√10)² - (√3)² = 10 - 3 = 7

Wykorzystanie wzory:

(a + b)² = a² + 2ab + b²

(a - b)(a + b) = a² - b²

(√a)² = | a |